Perception of land degradation and Indigenous land management practices in Mo basin watershed, Togo - DIWEDIGA, BADABATE; LE, QUANG BAO; EMMANUEL, OFORI; KPERKOUMA, WALA (Journal of Soil and Water Conservation, 2021)
This paper presents an investigation on the current state of, and the local level of awareness on, rural land degradation in Mo basin (Togo). Therefore, questionnaires were used to gather data using the professional farmer as unit of interview. In total, 108 key informants were interviewed. Farming characteristics and systems, the causes and indicators of land degradation (LD), and measures of land conservation were sought out to measure local opinions of land degradation. Questionnaire were made up of open-ended, close-ended and Likert-type questions. It was found that most of the land users are small-scale farmers. While land-related issues are perceived and discussed variously, majority of informants agreed that bushfire avoidance, agroforestry, and fallowing are the common land conservation best practices that should be observed by first-concerned land users. In order to combat land degradation, many farmers practice fallowing which duration (2 to 10 years) depends on the land availability of the farmers. Results also showed that farmers are highly aware that land degradation is a crucial threat to food security, poverty alleviation and social stability in rural communities. The farmers highlighted that criminality and non-respect of land-related community-rules are the major concerns affecting their daily efforts to adapted land use.